Optimizing Project Monitoring System in Holding Companies: A Strategic Framework for Sustainable Improvement - Yuni Pratidina Wijilestari; Santi Novani (Departemen Teknik Sipil ITS, 2025)
PT Pupuk Indonesia Holding Company (PIHC) is the largest fertilizer producer in Indonesia and one of the largest in Asia. PIHC plays a significant role in supporting agricultural demands. PIHC also increase its efficiency while still maintaining focus on sustainability. PIHC is currently managing several projects from its subsidiary that focusing in conservation on energy and production enhancement. PIHC manage its assets and investment. This study aims to optimize the project monitoring system in holding company through the development of a sustainable strategic framework. PIHC faces challenges in its project monitoring system such as inconsistent reporting formats, delayed information regarding project updates, and reliance on manual monitoring methods. The study adopts a qualitative approach using data collection method like in-depth interviews, internal document review, and literature studies. The findings from this study suggest that the implementation of an integrated digital dashboard and standardized reporting formar improved monitoring efficiency and support data-driven decision-making.